TRAINING AND USE OF INTERACTIVE POWER POINTS IN NATURAL EVENT MATERIAL FOR TEACHER PRIMARY SCHOOL AT MUHAMMADIYAH 1 PURWOREJO - Titi Anjarini; Galih Yansaputra (Universitas Sebelas Maret, 2018)
The purpose of community service activity is in the form of training of microsoft power point interactive utilization on natural event material for elementary school at Muhammadiyah 1 Purworejo teachers, among others: (1) teachers become skilled in developing computer-based teaching materials, (2) creating learning innovation in elementary school Muhammadiyah 1 Purworejo, (3) realization of computer-based learning in classroom learning activities, (4) improvement of quality and learning outcomes at Primary School Muhammadiyah 1 Purworejo, (5) scientific publication on utilization of Microsoft Power Point Interactive on Natural Event Material for Teachers SD Muhammadiyah 1 Purworejo, (6) mass media utilization of interactive microsoft power point on the material of natural events for Teachers of SD Muhammadiyah 1 Purworejo. The method applied by the community service activity is in the form of short training using lecture, discussion, question and answer method and the demonstration which was followed by 9 teachers held at SD Muhammadiyah 1 Purworejo which cover the planning, implementation, and production process.